The Influence Of The Brexit Phenomena On The British Economy - Maharanie, Popy; Argenti, Gili; Marsingga, Prilla (Jurnal Ilmiah Wahana Pendidikan, 2025)
Brexit stands for "British Exit", namely Britain's withdrawal from the European Union as a result of the Brexit referendum for its people to choose whether to remain in or leave the European Union.The European Union itself is the main regional institution created by several countries after the Second World War to achieve closer political and economic goals and to promote lasting reconciliation between France and Germany. This organization was officially established in 1993 with the signing of the Maastricht Treaty in Maastricht, Netherlands. The European Union is one of the largest multilateral organizations in the world because its members are sovereign and independent states, although they combine their sovereignty to achieve great collective power and influence. The occurrence of "Brexit" certainly affected the British economy, namely the decline in the sectortrade, employment, and industry.This study uses descriptive qualitative research and the data collection technique used by the author is a document study.